Domination et protestation: le sens de l’Acadianité - Thériault, J. Yvon (Anthropologica, 2022)
Starting with the definition of the "ethnic situation" as a meaningful relation within a society, the article indicates the social relations which contribute to transform that "ethnic situation" into a protest movement phenomene nationalitaire). Analyzing the history of the question acadienne (francophones of New Brunswick 1860-1980), the author establishes a periodisation which allows a reading of structural periods in some of which the "ethnic situation" is characterized by a relation of order (domination), and in others by social protest.